Resource depletion: where is an intervention most effective?. Issue 4 (2nd September 2019) - de Laat, Patrick
Abstract : Purpose: Where does one need to intervene in to be most effective? The purpose of this study is to rank areas of the resource system, according to how much of a change can be expected from interventions in an area, in relation to the problem of depleting resources. Design/methodology/approach: Principles of structured analysis are used to model how society uses resources. From this model, nine intervention areas are defined. These intervention areas are ranked in terms of effectiveness, through the use of the analytic hierarchy process. Findings: To be most effective, one must prioritize intervention areas as follows: material inputs to the operation phase; process inputs to the operation phase; products' longevity; process inputs to the manufacturing phase; and material inputs to the manufacturing phase. Practical implications: Most decisions are not made on the basis of rigorous analysis but by using heuristics (rules of thumb). The results of this study are expressed as rules of thumb. They can help decision makers prioritize what is most important, but without imposing new ways of working. Originality/value: In the construction domain, heuristics that generalize the impact of actions (content), instead of intervention areas (context), currently seem to prevail. The heuristics of this study generalize the impact of intervention areas. Therefore, they provide an extra perspective for many decision makers. This extra perspective can help reduce mistakes that are typically made by oversimplifying matters.